2016
DOI: 10.3389/fmicb.2016.01548
|View full text |Cite
|
Sign up to set email alerts
|

Genes Required for the Anti-fungal Activity of a Bacterial Endophyte Isolated from a Corn Landrace Grown Continuously by Subsistence Farmers Since 1000 BC

Abstract: Endophytes are microbes that inhabit internal plant tissues without causing disease. Some endophytes are known to combat pathogens. The corn (maize) landrace Chapalote has been grown continuously by subsistence farmers in the Americas since 1000 BC, without the use of fungicides, and the crop remains highly valued by farmers, in part for its natural tolerance to pests. We hypothesized that the pathogen tolerance of Chapalote may, in part, be due to assistance from its endophytes. We previously identified a bac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 71 publications
1
8
0
Order By: Relevance
“…Burkholderiaceae are considered keystone members in grasslands as endophytes or pathogens [83][84][85][86] and are known for their antimicrobial properties [87][88][89], nitrogen-fixing abilities [80,90], and competitive dominance, especially in N-limited environments [91]. Some members are even known to suppress fungal pathogens [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…Burkholderiaceae are considered keystone members in grasslands as endophytes or pathogens [83][84][85][86] and are known for their antimicrobial properties [87][88][89], nitrogen-fixing abilities [80,90], and competitive dominance, especially in N-limited environments [91]. Some members are even known to suppress fungal pathogens [92,93].…”
Section: Discussionmentioning
confidence: 99%
“…We then reconstructed the phylogeny of the 22 bacterial species based on these 763 single-copy core genes, and the results showed that CGB10 was closest to B. gladioli, and together they clustered with B. glumae (Figure 1A). We further confirmed the taxonomic status of CGB10 by calculating the average nucleotide identity (ANI) [28] based on the whole genome of the CGB10 strain in comparison with another six B. gladioli strains, including established rice pathogen BSR3 [24], strains isolated from healthy plants and displaying antifungal activity [29][30][31], and strains isolated from a cystic fibrosis patient [32], as well as a B. glume strain BGR1 [24], which is also known as a rice pathogen (information of selected strains was detailed in Table 1). The identity between CGB10 and the six selected B. gladioli strains was all higher than 98%, yet the identity between CGB10 and the B. glumae strain BGR1 was 88.12%.…”
Section: Genome Sequencing and Phylogenetic Analysis Of Cgb10mentioning
confidence: 62%
“…This family is considered a keystone member in grasslands and is often associated with plants as endophytes or pathogens [85][86][87][88]. Burkholderiaceae contains members known for their antimicrobial properties [89][90][91], nitrogen-fixing abilities [82,92], and competitive dominance, especially in N-limited environments [93] like serpentine. Some members of Burkholderiaceae are even known to suppress fungal pathogens including the turf grass pathogen Rhizoctonia (family Ceratobasidiaceae) [94,95].…”
Section: Discussionmentioning
confidence: 99%